Towards the Consolidation of a Diagramming Suite for Agent-Oriented Modelling Languages. (25th March 2013) - Henderson-Sellers, Brian
Abstract : Whilst several agent-oriented modelling languages have been developed by independent research groups, it is now appropriate to consider a consolidation of these various approaches. There are arguably three things that need consolidation and future standardization: individual symbols, the underpinning metamodel, and the diagram types. Here we address only the third issue by extending an earlier analysis that resulted in recommendations for various diagram types for the modelling of a multiagent system (MAS). Here, we take each of these previously recommended diagram types and see how each is realized in a wide variety (over 20) of current agent-oriented software engineering (AOSE) methodologies. We also take the opportunity to express, as exemplars, some of these diagram types using the recently published FAML notation.